Impact of Project-Based Learning for Improving Students Skills by Incorporating Design Thinking Process - Mahajan, Hema; Naik, Santosh Madeva; M., Sreeramulu; Kannaiah, Ch; Majeedullah, Syed (Journal of Engineering Education Transformations, 2021)
Engineering education is oriented towards active leaning & its implementation and hence project-based learning (PBL) plays a major role to enhance students learning practically. In this context, his study implemented PBL in the course projects for mechanical engineering students and students’ learning was investigated. Every project needs roadmap to follow for being on the desired path and gets fruitful outcomes and hence in this study design thinking process was introduced in the course during PBL which helped students to understand the real-time problems which can be solved by applying the knowledge gained theoretically from the courses. Through design thinking process, students got to know the real-time problems and improved their skills to deal with the same by applying their knowledge. Students have improved their understanding to handle real-time problems and at the same time they interacted with community partner that helped them to go in the depth to work on it. This study has shown the importance of design thinking process and its impact on student’s learning.